Lessons for parliament emanating from the state capture commission report: towards a reformed parliamentary oversight and accountability model - Tetyana, Andile (Department of Public Law, 2026)
This paper examines a topical issue that has occupied the minds of South Africans since President Zuma ascended to the highest office in the land in 2009 – State Capture. The paper does this by looking at the regulatory architecture of parliamentary oversight in terms of South Africa's constitutional scheme. This paper argues unchangingly that the Constitution, together with the Rules of Parliament, especially those of the National Assembly, empower Parliament to effectively exercise oversight over the Executive. Additionally, this paper looks at the current state of South Africa's parliamentary politics by placing a strategic focus on what presently obtains with the existing oversight and accountability instruments. The primary purpose of this is to look at which features of the current oversight and accountability dispensation require improvements and which aspects require an overhaul. Furthermore, the paper critically examines the recommendations of the Zondo Report on parliamentary oversight, the spotlight here being on the proposed reforms which the Zondo Commission has mooted as a way of bolstering the current model. Moreover, this paper looks at the scope and ambit of parliamentary oversight. The emphasis here is on what the limits of oversight are and how far can Parliament go if members of the Executive ignore House resolutions that have been adopted by the legislative branch of government? Here, this paper grapples with concepts like amendatory accountability in the context of the doctrine of separation of powers and South Africa's constitutional architecture in general. Finally, a strategic case is made for the need for institutional and regulatory reforms. These proposed reforms build on what is already provided for in the regulatory architecture of South Africa's constitutional scheme. To this end, this paper postulates that ours is not a problem of policy or law, but that of leadership. In conclusion, this paper provides demonstrable proof that for effective oversight to be realized, subjective factors in the form of political will and principled leadership will have to be very much part of the basket of solutions in this regard.